Developmental Expression Patterns of Tbx1, Tbx2, Tbx5, and Tbx20 in Xenopus tropicalis - Showell, Chris (2006)
T-box genes have diverse functions during embryogenesis and are implicated in several human congenital disorders. Here, we report the identification, sequence analysis, and developmental expression patterns of four members of the T-box gene family in the diploid frog Xenopus tropicalis. These four genes—Tbx1, Tbx2, Tbx5, and Tbx20—have been shown to influence cardiac development in a variety of organisms, in addition to their individual roles in regulating other aspects of embryonic development. Our results highlight the high degree of evolutionary conservation between orthologs of these genes in X. tropicalis and other vertebrates, both at the molecular level and in their developmental expression patterns, and also identify novel features of their expression. Thus, X. tropicalis represents a potentially valuable vertebrate model in which to further investigate the functions of these genes through genetic approaches.